Incremental value of computed tomography perfusion for final infarct prediction in acute ischemic cerebellar stroke - Fabritius, Matthias P.; Kellert, Lars (Journal of the American Heart Association, 2019)
BackgroundThe diagnosis of ischemic cerebellar stroke is challenging because of nonspecific symptoms and very limited accuracy of commonly applied computed tomography (CT) imaging. Advances in CT perfusion imaging provide increasing value in the detection of posterior circulation stroke, but the prognostic value remains unclear. We aimed to identify imaging parameters that predict morphologic outcome in cerebellar stroke patients using advanced CT including whole‐brain CT perfusion (WB‐CTP).Methods and ResultsWe selected all subjects with cerebellar WB‐CTP perfusion deficits and follow‐up‐confirmed cerebellar infarction from a consecutive cohort with suspected stroke who underwent WB‐CTP. Posterior‐circulation‐Acute‐Stroke‐Prognosis‐Early‐CT‐Score (pc‐ASPECTS) was determined on noncontrast CT, CT angiography source images, and on parametric WB‐CTP maps. Cerebellar perfusion deficit volumes on all maps and the final infarction volume on follow‐up imaging were quantified. Uni‐ and multivariate regression analyses were performed. Sixty patients fulfilled the inclusion criteria. pc‐ASPECTS on CT angiography source images (ß, −9.239; 95% CI, −14.220 to −4.259; P<0.001) and cerebral blood flow deficit volume (ß, 0.886; 95% CI, 0.684 to 1.089; P<0.001) were significantly associated with final infarction volume in univariate linear regression analysis. The association of cerebral blood flow deficit volume (ß, 0.830; 95% CI, 0.605-1.055; P<0.001) was confirmed in a multivariate linear regression model adjusted for age, sex, pc‐ASPECTS on noncontrast CT, and CT angiography source images and the National Institutes of Health Stroke Scale score on admission. No other clinical or imaging parameters were associated with cerebellar stroke final infarction volume (P>0.05).ConclusionsIn contrast to noncontrast CT and CT angiography, WB‐CTP imaging contains prognostic information for morphologic outcome in patients with acute cerebellar stroke.
Gesehen am 09.01.2020